Fanatical Military Recruiting - Blount, Jeb (Ascent Audio, 2019)
Smart, competent, and capable people are rare and in high demand. Every organization-from commercial enterprises, healthcare, non-profit, sports, education, to the military-is in an outright battle to recruit and retain these bright and talented people. Rather than bullets and bombs, the war for talent is won through high-impact prospecting activity, time discipline, intellectual agility, emotional intelligence, and human to human relationships. On this highly competitive, ever changing, asymmetric battle field, to win, you must operate a level of excellence beyond anything asked of military recruiters before. Yet, in this new paradigm, many recruiters are struggling, and most recruiting units are staring down the barrel at 50 percent or more of their recruiters consistently missing Mission. It is imperative that we arm military recruiters with the skills they need to win in this challenging environment. The failure to make Mission is an existential threat to the strength and readiness of America's fighting forces and our democracy. Fanatical Military Recruiting begins where the Recruiting and Retention colleges of the various branches of the military leave off. It is an advanced, master's level training resource designed specifically for the unique demands of Military Recruiting.